Effectiveness of an Instructional Program on Nurses-Midwifes' Practices about Application of Ethical Rules at the Delivery Room - Khairyah Hussein Salman, Sadeq Al-Fayyadh, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nurse midwives are often expected to make ethical decisions in the context of their professional practice, which can lead to ethical confrontations, some of which may lead to ethical dilemmas. The nurses and midwives in the delivery room must keep ethical considerations in mind while caring for a woman in labor so that correct judgments can be made. As a result, the current study emphasized raising ethical efficacy by creating scenarios that simulate the reality of working in the field of reproductive health in order to prepare nurse-midwives who comply with ethical rules during professional practice. Purpose: The main aim of this study is examining how an instructional nursing professional ethics-focused program may affect practice among nurses- midwives in the delivery room. Methods: The quiz experimental design (one-group pretest–posttest design) was used. The purposive non-probability sample consisted of 50 nurse-midwives who worked during the data collection phase in the delivery room. Data collection began in May 2021 - June 2022, using a tool that contains 20 case-scenario that simulate the reality of reproductive care and clinical practice of nurses and midwives regarding professional ethical issues Results: The findings revealed that instructional intervention had a positive impact on nurses - midwife's ethical performance in terms of following professional ethics rules Conclusion: The use of the case-scenario based simulation approach to teach professional nursing ethics contributed to improving compliance with the ethical rules for nurses-midwives working in the delivery room